PRT-060318, a novel Syk inhibitor, prevents heparin-induced thrombocytopenia and thrombosis in a transgenic mouse model - Reilly, Michael P. (American Society of Hematology, 2011)
Heparin-induced thrombocytopenia (HIT) is a major cause of morbidity and mortality resulting from the associated thrombosis. Extensive studies using our transgenic mouse model of HIT have shown that antibodies reactive with heparin-platelet factor 4 complexes lead to FcγRIIA-mediated platelet activation in vitro as well as thrombocytopenia and thrombosis in vivo. We tested PRT-060318 (PRT318), a novel selective inhibitor of the tyrosine kinase Syk, as an approach to HIT treatment. PRT318 completely inhibited HIT immune complex-induced aggregation of both human and transgenic HIT mouse platelets. Transgenic HIT model mice were treated with KKO, a mouse monoclonal HIT-like antibody, and heparin. The experimental group received orally dosed PRT318, whereas the control group received vehicle. Nadir platelet counts of PRT318-treated mice were significantly higher than those of control mice. When examined with a novel thrombosis visualization technique, mice treated with PRT318 had significantly reduced thrombosis. The Syk inhibitor PRT318 thus prevented both HIT immune complex-induced thrombocytopenia and thrombosis in vivo, demonstrating its activity in HIT.